The Role of the Principal in Strengthening Character Education in School By Involving Tripusat Pendidikan - Nasrika, Nasrika; Zulkarnain, Wildan; Sunarni, Sunarni (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2021)
Abstract: This study describes: (1) the role of the principal in the implementation of character education in schools; (2) the involvement of "tri pusat pendidikan" in supporting the implementation of strengthening character education in schools; (3) the importance of strengthening character education in schools. This study aims to determine the role of the principal in maximizing the strengthening of character education in schools by involving the role of the "tri center of education" to obtain maximum results. Character education cannot be separated from the role of the family environment and the community environment so that the roles of the three environments are interrelated. Character education applied in schools is carried out using the concept of self-discipline which will shape the personality of students through habituation. Schools in implementing character education also involve the role of the community and parents to participate in character education in schools. This study uses a descriptive qualitative approach and the type of case study research. The data collection process carried out in this study was carried out by interviews, observation, and documentation. Keywords: Leadership, tripusat pendidikan, character education